Motivasi dan Prestasi Belajar Mahasiswa Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Palangka Raya di Tengah Pandemi COVID-19 Tahun 2020 - Sri Rohaetin; Kartini Kartini (Jurnal Ilmiah Kanderang Tingang, 2021)
This research is motivated by the learning motivation of students of the Economic Education Study Program FKIP Palangka Raya University during the COVID-19 pandemic. In compiling lecture assignments, each student has their learning methods and techniques, especially to achieve success in learning achievement. The purpose of this study is to determine the motivation and learning achievement of students of Economics Education FKIP Palangka Raya University during the COVID-19 pandemic. This study uses a qualitative approach, with a descriptive method. The results of research conducted at the Economic Education Study Program, Faculty of Teacher Training and Education, Palangka Raya University are about the motivation and learning achievement of Economic Education students, which indicated by the results of interviews that researchers have conducted, namely with the results of the research, most of the students of the Economics Education Study Program have high intrinsic and extrinsic motivation in achieving learning achievement. So, students have a strong willingness in carrying out learning activities. This can be seen from the average Economic Education students who got high Indeks Prestasi Semester or Grade Point Average (GPA) score from last semester, wherein the even semester of 2020/2021 lectures had used the online or online method.